2019
DOI: 10.1016/j.cub.2019.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms Coordinate Soil Biota to Improve Multiple Ecosystem Functions

Abstract: Highlights d Earthworms enhanced multifunctionality by indirect rather than direct effects d Earthworms shifted functional composition toward bacterialdominated community d Multifunctionality was unrelated to changes in soil biodiversity, structure, and pH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 70 publications
3
42
0
1
Order By: Relevance
“…Such studies conducted on both terrestrial (e.g. kangaroo rats [66], earthworms [67]) and aquatic organisms (e.g. carp [68], crayfish [69]) have proven their value in studying the ecosystem engineer concept.…”
Section: (C) Consequences On Trophic and Non-trophic Relationshipsmentioning
confidence: 99%
“…Such studies conducted on both terrestrial (e.g. kangaroo rats [66], earthworms [67]) and aquatic organisms (e.g. carp [68], crayfish [69]) have proven their value in studying the ecosystem engineer concept.…”
Section: (C) Consequences On Trophic and Non-trophic Relationshipsmentioning
confidence: 99%
“…But, both S21 and SE gave the higher weight than S, which could be due to the activities of both earthworms and microorganisms involved in the two treatments (SE and S21). Numerous studies on the interactions between earthworms and soils' microbial communities have demonstrated the beneficial role of earthworms on pedogenesis and soil quality and its implications on the increase in plant biomass (Jacquiod et al, 2020;Liu et al, 2019;Rodriguez-Campos et al, 2014). Recently, Guhra et al (2020) observed a preferential adsorption of the organic carbon and organic phosphorus compounds in the earthworms' mucus on soil minerals which could enrich the newly-formed organo-mineral associations with biogenic nutrient elements.…”
Section: Vegetative Growth Parameters Of Phaseolus Vulgaris Lmentioning
confidence: 99%
“…Earthworms (Lumbricidae) constitute the majority of soil faunal biomass in many temperate agroecosystems with up to 1000 individuals and 300 g of biomass in each square metre of land [34,35]. They modulate agroecosystem function by affecting nutrient cycling and decomposing organic material [36,37], recovering soil carbon pools after disturbance [38], maintaining soil microbial diversity [39,40], controlling plant pathogens [41][42][43], influencing water infiltration, and interacting with above ground organisms [44][45][46][47]. Thus, any herbicide-induced effect on earthworm activity will impact these ecosystem functions and influence water infiltration, and the binding and leaching of glyphosate [48].…”
Section: Introductionmentioning
confidence: 99%